1999
DOI: 10.1038/sj.jp.7200145
|View full text |Cite
|
Sign up to set email alerts
|

Seizure and Electroencephalographic Changes in the Newborn Period Induced By Opiates and Corrected By Naloxone Infusion

Abstract: OBJECTIVE:To describe the association between opioid administration in the newborn period and neurologic abnormalities STUDY DESIGN:Case reports of two infants who presented with seizure activity and abnormal electroencephalograms associated with opiate administration, and reversed by naloxone RESULTS:The first was a preterm infant who developed a burst-suppression pattern on the electroencephalogram while receiving a continuous infusion of morphine and muscle paralysis. Naloxone injection during the electroen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 9 publications
1
4
1
Order By: Relevance
“…In another previous experimental study, it has been shown that naloxone could increase the seizurogenic dose of heroin, d-propoxyphene, meperidine and normeperidine, and a convulsant inhibitory effect of naloxone is suggested as a result 10. Furthermore, in a previous case report, naloxone could control the seizures following continuous infusion of morphine and fentanyl in two newborns whose seizures were not controlled by administration of antiepileptic drugs 14. As we observed, many of the participants of this study did have abnormal CSM waves, low CSI, and low OD, which indicated that the patients might have seizure without any clinically obvious convulsion presenting with postseizure complaints.…”
Section: Discussionsupporting
confidence: 52%
“…In another previous experimental study, it has been shown that naloxone could increase the seizurogenic dose of heroin, d-propoxyphene, meperidine and normeperidine, and a convulsant inhibitory effect of naloxone is suggested as a result 10. Furthermore, in a previous case report, naloxone could control the seizures following continuous infusion of morphine and fentanyl in two newborns whose seizures were not controlled by administration of antiepileptic drugs 14. As we observed, many of the participants of this study did have abnormal CSM waves, low CSI, and low OD, which indicated that the patients might have seizure without any clinically obvious convulsion presenting with postseizure complaints.…”
Section: Discussionsupporting
confidence: 52%
“…Although CNS effects are more common with meperidine, they have also been reported with other opioids including morphine, fentanyl, alfentanil, and remifentanil. [1114] As with chest wall rigidity, the CNS effects are thought to be related to excitation of pyramidal neurons of the hippocampus due to inhibition of interneurons of the GABA system.…”
Section: Adverse Effects Of Sedative and Analgesic Agentsmentioning
confidence: 99%
“…Only a few articles discuss the effect of morphine on the EEG in the neonate. Da Silva et al described two infants who developed epileptiform activity after opiate administration (8). When naloxone was administered and opiate administration was stopped, epileptiform activity was reduced.…”
Section: Discussionmentioning
confidence: 99%